Current and future intensity-duration-frequency curves based on weighted ensemble GCMs and temporal disaggregation - Nasidi, Nuraddeen Mukhtar; Aimrun Wayayok,; Ahmad Fikri Abdullah,; Muhamad Saufi Mohd Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Hydrological events are expected to increase in both magnitude and frequency in tropical areas due to climate variability. The Intensity – Duration – Frequency (IDF) curves are important means of evaluating the efficiency of irrigation and drainage systems. The necessity to update IDF curves arises from the need to gain better understanding of the impacts of climate change. This study explores an approach based on weighted Global Circulation Models (GCMs) and temporal disaggregation method to develop future IDFs under Representative Concentration Pathways (RCP) emission scenarios. The work consists of 20 ensemble GCMs, three RCPs (2.6, 4.5, and 8.5) and two projection periods (2050s and 2080s). The study compared three statistical distributions and selected Generalized Extreme Value (GEV) being the best fitting distribution with baseline rainfall series and therefore used for IDF projection. The result obtained shows that, the highest rainfall intensities of 19.32, 35.07 and 39.12 mm/hr occurred under 2-, 5-, and 20 years return periods, respectively. IDFs from the multi-model ensemble GCMs have shown increasing intensity in the future for all the return periods. This study indicated that the method could produce promising results which can be extended to other catchments.